Czy ekonomia jest nauką? - Czerwiński, Zbigniew (Wydział Prawa i Administracji UAM, 1996)
There is no universally accepted definition of science that would fit the very differentiated field of research, comprising, among others, mathematics, physics, biology, psychology, archaeology, economics, etc. It is, therefore, easy to define science in such a way that some fields od research will fall under the category of science and the others will not. If (as it was in vogue among positivists and physicalists) we recognize as the model-science physics with its universal and exact (as a rule quantitative) laws, valid independently of time and space, economics would have to be located outside the scope of science, because it is unable to discover such laws in the behaviour of economic agents (unless they are trivial or purely analytical). This is due to the fact that economic agents (producers, consumers), as human beings, do not react to the impulses coming from the setting in which they find themselves as regularly and automatically as physical objects. Economic agents adapt their current behaviour to their changeable aims, taking into account results of their past behaviour which brought them success or failure. Keeping in memory all their past, they constantly learn, and modify their reactions to impulses, if they think another reaction will this time be better. Besides, the whole natural, technical, and institutional setting of economic activity constantly changes. This is why physical science does not seem to be an appropriate model of economic science. The idea of the unity of science, expecting all sciences to more or less follow the pattern created by physics is unfeasible. Economics seems to be able to discover only propositions of "local" character, valid only in some narrow time-space interval which, incidentally, makes it hard or even impossible to transfer scientific achievements of economists from one country to another, contrary to relatively easy transfer of the results of physical science.
Is economics a science?